Zelo Zelatus Praise And Worship Sebagai Sarana Katekese Yang Cocok Bagi Kaum Muda - Caroline Resthy Wardhani Halawa; Intansakti Pius X (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
This research examines the issues of active participation of young Catholics in the life of the church, particularly facing challenges posed by technological advancements, a trend of waning interest in religion, and boredom with traditional religious activities. In addressing this reality, the research explores the potential of Zelo Zelatus Praise and Worship as a suitable catechesis tool for young people. The research methodology employed is a literature review with a focus on literature discussing the current church life of young people, Zelo Zelatus Praise and Worship, and catechesis as a suitable tool for fostering faith among the youth. The findings of the research indicate that the church life of young people today is characterized by busy lifestyles and a lack of interest in traditional liturgy. Young people tend to seek more dynamic and contemporary religious experiences. Zelo Zelatus Praise and Worship, with its emphasis on praise and worship, emerges as an attractive alternative for young people to develop their faith and explore their spirituality. The research also highlights the urgency of catechesis as an effort to nurture faith among the youth. Effective catechesis should be responsive to the needs and dynamics of young people, building connections between faith and daily life. Zelo Zelatus Praise and Worship is identified as a potential catechesis tool that aligns with the spiritual needs of the youth through a more dynamic and inclusive approach.